The Effect of Pocket Book on Kangaroo Care Method for Mothers Giving Birth to Babies Weighing - Siti Rahmayanti; Oon Fatonah Akbarini; Dianna Dianna (Borneo Scientific Publishing, 2026)
Low Birth Weight (LBW) is defined as a birth weight of less than 2,500 grams regardless of gestational age, measured within one hour after birth. Globally, the prevalence of LBW reaches approximately 21% of all births. In Landak District, the incidence of LBW fluctuated from 4.5% in 2020 to 2.6% in 2021 and increased again to 5.0% in 2022. Kangaroo Care (KC) is an effective method for improving the survival and health outcomes of LBW infants; however, its implementation requires adequate maternal knowledge and skills. Educational media, such as pocket books, can facilitate learning by making information easier to understand and remember. This study aimed to determine the effect of pocket book-based education on mothers’ knowledge and skills regarding Kangaroo Care among mothers who gave birth to LBW infants in Landak Regency. This study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 22 respondents were selected using consecutive sampling. Data were analyzed using the Wilcoxon signed-rank test. The results showed a significant improvement in both knowledge and skills after the intervention, with p-values of <0.001. In conclusion, pocket book-based education is effective in improving mothers’ knowledge and skills regarding Kangaroo Care among mothers with LBW infants in Landak Regional General Hospital.